Apology and Forgiveness as a Mechanism of Resilience and as a Factor in the Restorative Process - Pavićević, Olivera; Ilijić, Ljeposava; Bulatović, Aleksandra (Zbornik Instituta za kriminološka i sociološka istraživanja, 2017)
The relationship between the individual and social level of resilience can also be viewed via apology and forgiveness as a factor in the initiation and design of the restorative process. Reviewing the key components of the apology and forgiveness process provides insight into the relationship between the moral and legal bases of apology, as outlined by the perspective of the interaction between moral values that dominate in society and its legal system. Analyzing the process of apology and forgiveness in the framework of individual, social and legal communication, the authors find arguments that point to the significance of this process for developing resistance within the framework of social and legal practice relying on the principles of restorative justice. The aim of the paper is to suggest that individual resistance based on morality is one of the factors of social competence.